Exploration of highly selective fluorogenic 'on–off' chemosensor for H2PO4− ions: ICT‐based sensing and ATPase activity profiling. (16th December 2019) - Wagh, Yogesh B.; Tayade, Kundan C.; Kuwar, Anil; Sahoo, Suban K.; Mayank,; Singh, Narinder; Dalal, Dipak S.
Abstract: Abstract In this study, the recognition contour of Chemosensor 1 was investigated using semiaqueous methanol (XH, mole fraction = 0.31) for a range of anions and bioactive species. Host–receptor signalling based on the internal charge transfer mechanism for Chemosensor 1 was explored and reported. Structure of Chemosensor 1 and its plausible anion coordination based on hydrogen bonding is complemented with density functional theory. Consequently, we investigated the applicability of the synthesized probe in blood plasma, urine, tap water samples, and for monitoring of ATP in lysosomes by apyrase enzyme.